Regeneration and Transformation via Agrobacterium tumefaciens of Echinacea purpurea L. (Plant Tissue Culture and Biotechnology, 2011)
Leaf explants of Echinacea purpurea L. taken from aseptically germinated seedlings were inoculated with A. tumefaciens strains EHA105, carrying a binary vector conferring herbicide resistant bar gene and fungal resistant chitinase gene. Glufosinate ammonium-resistant shoots were regenerated on a medium containing BAP and NAA at a concentration of 4.88 and 0.053 µM, respectively. A subsequent transfer of shoots to medium containing BAP was necessary for stem elongation and leaf development. Transgenic Echinacea plants carrying bar and chitinase genes were selected for their resistance to glufosinate ammonium herbicide. Molecular analysis using PCR confirmed the integration of the transgenes into plant genome. This is the first report on genetic transformation of Echinacea plant using bar gene as a selectable marker. Key words: Echinacea purpurea; Regeneration; A. tumefaciens; Transformation D.O.I. 10.3329/ptcb.v20i2.6888 Plant Tissue Cult. & Biotech. 20(2): 101-111, 2010 (December)